2004
DOI: 10.1128/jcm.42.9.4332-4334.2004
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation of the cppB Gene as a PCR Target for Detection of Neisseria gonorrhoeae

Abstract: The cppB gene is often used as a target for detection of Neisseria gonorrhoeae by PCR. Using a coded panel of 500 DNA samples, we determined that the cppB gene is missing in 5.8% of N. gonorrhoeae strains, and therefore we consider the cppB gene to be an unsuitable target

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 15 publications
1
34
1
Order By: Relevance
“…However, subsequent melting curve analysis clearly distinguished NgNS from N. gonorrhoeae, with the N. gonorrhoeae T m always being above 64°C and the NgNS T m always being below 57°C. These results were confirmed in a study in which 450 well-characterized N. gonorrhoeae strains interspersed with negative controls and 20 NgNS strains were tested (2).…”
Section: Resultssupporting
confidence: 67%
“…However, subsequent melting curve analysis clearly distinguished NgNS from N. gonorrhoeae, with the N. gonorrhoeae T m always being above 64°C and the NgNS T m always being below 57°C. These results were confirmed in a study in which 450 well-characterized N. gonorrhoeae strains interspersed with negative controls and 20 NgNS strains were tested (2).…”
Section: Resultssupporting
confidence: 67%
“…Recently, two independent studies investigated the use of N. gonorrhoeae cppB PCR assays on populations in Australia and the Netherlands. 50, 51 Tabrizi et al 51 found no false-negative results and considered the cppB gene assay to be suitable for use in a population in Victoria, Australia, whereas Bruisten et al 50 found a high incidence (5.8%) of false-negative results and concluded that the cppB gene target was not suitable for use in the Dutch population. Interestingly, other Australian studies have revealed a high incidence of cppB-related false-negative PCR results in a patient population in the Northern Territory in Australia, due to the recent appearance and expansion of a non-PAU Ϫ gonococcal subtype.…”
Section: Sequence-related Challenges For Gonorrhea Naat Assaysmentioning
confidence: 99%
“…However, cppB gene-based NAAT assays are now no longer considered adequate for some patient populations because of the limitations outlined previously. 50 More recently, a PCR assay targeting the N. gonorrhoeae porA pseudogene showed considerable promise as a suitable supplementary test for the Amplicor assay. 91 So far, this assay has only been validated in an Australian population and will need further validation in other populations.…”
Section: Roche Cobas Amplicormentioning
confidence: 99%
See 1 more Smart Citation
“…Further, considerable recombination occurs within the DNA of the plasmid and some cppB gene sequences present in the chromosome were incomplete and in low copy numbers (6,7). It is thus not surprising that some decreased sensitivity with cppB gene-based nucleic acid amplification, arising from absent, altered, or low copy numbers of the chosen sequence, has now been acknowledged with different forms of this test (2,9).…”
mentioning
confidence: 99%